2018
DOI: 10.3389/fchem.2018.00375
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Isolation of a Polyoxocation Mimicking Vanadium(V) Oxide Layered-Structure by Stacking of [H2V2O8]4− Anions Bridged by (1,4,7-Triazacyclononane)Co(III) Complexes

Abstract: An isolation of a vanadium(V) oxide cluster mimicking V2O5 layered structure was achieved formulated as [{Co(tacn)}4V4O12(OH)4]4+ (1) (tacn = 1,4,7-triazacyclononane). From the 51V NMR spectra of the reaction mixtures, we optimized the reaction condition in terms of a molar ratio of VO43− and [Co(tacn)(H2O)3]3+ as well as a pH value. Cluster 1 is stable in a wide range of pH values from 1.5 to 8.0, and the presence of multiple hydrogen bondings in the structure is a unique feature. In the X-ray analysis of clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In this way, SEL is able to overcome a larger ability of RAS to form hydrogen bonds that only position it in less reactive orientations for the subsequent inhibition reaction. More importantly, this was followed by the quantum mechanics (QM) cluster calculations [ 54 ] at the DFT level, which revealed that the MAO inactivation proceeded through a three-step reaction, where, in the rate-limiting first step, the MAO enzyme used the FAD’s N5 atom to abstract a hydride anion from the inhibitor’s α-CH 2 group ( Figure 2 ), being in a full analogy with the MAO catalytic mechanism [ 55 , 56 , 57 , 58 ], thus confirming that both SEL and RAS are mechanism-based inhibitors. The complete reaction profile led from the bound inhibitors to the corresponding N5(FAD)-adducts, the latter being in excellent agreement with the crystallographic data on the inhibited enzyme, and further confirmed a better reactivity of SEL through both its lower activation barrier and higher overall exergonicity [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, SEL is able to overcome a larger ability of RAS to form hydrogen bonds that only position it in less reactive orientations for the subsequent inhibition reaction. More importantly, this was followed by the quantum mechanics (QM) cluster calculations [ 54 ] at the DFT level, which revealed that the MAO inactivation proceeded through a three-step reaction, where, in the rate-limiting first step, the MAO enzyme used the FAD’s N5 atom to abstract a hydride anion from the inhibitor’s α-CH 2 group ( Figure 2 ), being in a full analogy with the MAO catalytic mechanism [ 55 , 56 , 57 , 58 ], thus confirming that both SEL and RAS are mechanism-based inhibitors. The complete reaction profile led from the bound inhibitors to the corresponding N5(FAD)-adducts, the latter being in excellent agreement with the crystallographic data on the inhibited enzyme, and further confirmed a better reactivity of SEL through both its lower activation barrier and higher overall exergonicity [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…The observed changes in peak positions during heating were caused by the loss of lattice water molecules in the structure, which produced a rearrangement of the hydrogen bonding network. This fluctuation in hydrogen bondings was most likely reflected in the reversible change in the coordination environment of Co­(III) centers, and the similar thermochromic behavior was found in {[Co III (tacn)] 4 V 4 O 12 (OH) 4 } (tacn = 1,4,7-triazacyclononane) cluster …”
Section: Results and Discussionmentioning
confidence: 99%
“…We have been developing a new synthetic strategy that uses inert half-sandwich metal complexes such as the fac -[Co III (tacn)­(OH 2 ) 3 ] 3+ cationic complex and fac -[Mo VI (tacn)­O 3 ] neutral complex (tacn = 1,4,7-triazacyclononane) as chemical protecting groups to control the polymerization of metal ions in aqueous solution. By using fac -[Co III (tacn)­(OH 2 ) 3 ] 3+ , we have established new acid-condensation pathways for molybdate and vanadate anions, allowing us to isolate several metastable isopolyoxomolybdate, heteropolyoxomolybdate, and isopolyoxovanadate anions . While one face of the coordination sphere on fac -[Co III (tacn)­(OH 2 ) 3 ] 3+ is blocked by a strongly coordinating tacn macrocycle, the opposite face has three aquo leaving groups that can dissociate to give a free facial site, and the {Co III (tacn)} 3+ cation can sit on the peripheral of the polyoxometalates to block any further acid-condensation processes.…”
Section: Introductionmentioning
confidence: 99%